Type M Resistance to Macrolides Is Due to a Two-Gene Efflux Transport System of the ATP-Binding Cassette (ABC) Superfamily - Iannelli, Francesco; Santoro, Francesco; Santagati, Maria; Docquier, Jean-Denis; Lazzeri, Elisa; Pastore, Gabiria; Cassone, Marco; Oggioni, Marco R.; Rossolini, Gian M.; Stefani, Stefania; Pozzi, Gianni (Frontiers in Microbiology, 2018)
The mef(A) gene was originally identified as the resistance determinant responsible for type M resistance to macrolides, a phenotype frequently found in clinical isolates of Streptococcus pneumoniae and Streptococcus pyogenes. MefA was defined as a secondary transporter of the Major Facilitator Superfamily driven by proton-motive force. However, when characterizing the mef(A)-carrying elements Tn1207.1 and Φ1207.3, another macrolide resistance gene, msr(D), was found adjacent to mef(A). To define the respective contribution of mef(A) and msr(D) to macrolide resistance, 3 isogenic deletion mutants were constructed by transformation of a S. pneumoniae strain carrying Φ1207.3: (i) Δmef(A)-Δmsr(D); (ii) Δmef(A)-msr(D); (iii) mef(A)-Δmsr(D). Susceptibility testing of mutants clearly showed that msr(D) is required for macrolide resistance, while deletion of mef(A) produced only a 2-fold reduction in the MIC for erythromycin. The contribution of msr(D) to macrolide resistance was also studied in S. pyogenes, which is the original host of Φ1207.3. Two isogenic strains of S. pyogenes were constructed: (i) FR156, carrying Φ1207.3, and (ii) FR155, carrying Φ1207.3/Δmsr(D). FR155 was susceptible to erythromycin, whereas FR156 was resistant, with a MIC value of 8 µg/ml. Complementation experiments showed that reintroduction of the msr(D) gene could restore macrolide resistance in Δmsr(D) mutants. Radiolabelled erythromycin was found to be retained by strains lacking msr(D), while msr(D)-carrying strains showed erythromycin efflux. Deletion of mef(A) did not affect erythromycin efflux. This data suggest that type M resistance to macrolides in streptococci is due to an efflux transport system of the ATP-binding cassette (ABC) superfamily, in which mef(A) encodes the transmembrane channel, and msr(D) the two ATP-binding domains.